2008
DOI: 10.1016/j.socscimed.2008.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, social inequality, and HIV risk disclosure among Dominican male sex workers

Abstract: Some quantitative behavioral studies in the USA have concluded that bisexually behaving Latino men are less likely than White men to disclose to their female partners that they have engaged in same-sex risk behavior and/or are HIV-positive, presumably exposing female partners to elevated risk for HIV infection. Nevertheless, very little theoretical or empirical research has been conducted to understand the social factors that promote or inhibit sexual risk disclosure among Latino men who have sex with men (MSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 33 publications
5
65
0
1
Order By: Relevance
“…Their findings highlight that efforts to combat stigma and prejudice will be ineffective if they do not account for multiple and interlocking identities (Crenshaw, 1996). The paper by Padilla et al (2008) is also illustrative of why attention to multiple disadvantaged statuses is important to identifying the root causes of health disparities. In their work on bisexual Dominican male sex workers they find multiple disadvantaged statuses have important consequences for HIV risk.…”
Section: Bridging Stigma and Prejudice Research Traditionsmentioning
confidence: 99%
“…Their findings highlight that efforts to combat stigma and prejudice will be ineffective if they do not account for multiple and interlocking identities (Crenshaw, 1996). The paper by Padilla et al (2008) is also illustrative of why attention to multiple disadvantaged statuses is important to identifying the root causes of health disparities. In their work on bisexual Dominican male sex workers they find multiple disadvantaged statuses have important consequences for HIV risk.…”
Section: Bridging Stigma and Prejudice Research Traditionsmentioning
confidence: 99%
“…In Jamaica, cross-sectional surveys conducted with MSM in 2007 (n = 201) [12] and 2011 (n = 449) [2] identified the prevalence of sex-selling as 35.9% overall [2], and 30.5% and 39.4% among HIV negative and positive persons, respectively [12]. In contexts with pervasive sexual stigma and discrimination, MSM may experience limited access to education and employment, and may lose familial support; this may contribute to poverty, homelessness, and engagement in survival sex work for money in addition to food, rent, shelter, drugs, and/or alcohol [5,6,20,25]. …”
Section: Introductionmentioning
confidence: 99%
“…Significant knowledge gaps remain, however, regarding factors associated with selling sex, including multivariable analyses that identify independent effects of multi-level factors, and the possible association between sexual stigma and sex-selling among MSM in Jamaica [2]. Stigma is a particularly important area to examine among MSM who sell sex, who may face intersecting stigma, including sexual stigma, and HIV-related stigma, in addition to sex work stigma [4,5,3438]. Stigma has been identified as a barrier for male sex workers in accessing HIV prevention services [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process may be a coping strategy by which participants managed the stigma from non-conformance with masculine norms (Kong 2009). Kong (2009) participants spoke about stigma arising from morality and subordination, among other factors, and escorts in other studies indicated stigma arising from homosexuality (Koken et al 2004;Padilla et al 2008). However, none of the participants in this study reported stigma arising from any of these sources.…”
Section: Discussionmentioning
confidence: 50%